Diffusion of Digital Technologies towards NPA Management - Dr. S. Dinesh, Dr. M. Ananthi, Dr. S. T. Surulivel, Dr. R. Rengarajan (International Journal of Advanced Science and Technology, 2020)
Digital technologies today are disrupting and repositioning the lives of every banker and customer. According to RBI data, on 31 August 2018, 48.3% of the loan book of some of the large Indian scheduled commercial banks (SCBs), taken together, consisted of corporate assets. The remaining 51.7% is spread between micro, small and medium enterprises (MSMEs), retail customers and others. This study has mainly focussed on the bankers’ perspective of preventive measures using digital technologies to manage NPA. This study is the nature of descriptive research design. Both primary and secondary data used for study purpose. Eighty bankers were responded for this study and research adopted snowball sampling technique to gather the data. Major finding of this study are: Majority of the bankers are strongly agreeing about 90.6 % that adoption of obsolete technology was the foremost reason for the failure of borrowers and it was ranked as first in the reason for insolvency of borrowers. Lowest standard deviation of 0.42 was observed in this variable. It shows that majority of the bankers are considering without much variation in their opinion. Majority of the bankers are strongly agreeing about 93.6 % that lack of effective NPA management was the foremost reason for the failure of bankers and it was ranked as first in the reason for NPA. Lowest standard deviation of 0.42 was observed in this variable. It shows that majority of the bankers are considering without much variation in their opinion. Majority of the bankers are strongly agreeing about 92.4 % that CIBIL score was the foremost technology used by the bankers as preventive measures to control NPA. Framing cohesive & conducive regulatory regime. RBI should be more liberal in IRAC norms when the economy is on downturn; particularly for those sectors; which are severely affected due to economy slump & political scam; such as coal based industries, infrastructure, textile, aviation, etc.